Role of two RpoN in Bradyrhizobium sp. strain DOA9 in symbiosis and free-living growth - Wongdee, Jenjira; Piromyou, Pongdet; Songwattana, Pongpan; Greetatorn, Teerana; Teaumroong, Neung; Boonkerd, Nantakorn; Giraud, Eric; Nouwen, Nico; Tittabutr, Panlada (Frontiers in Microbiology, 2023)
RpoN is an alternative sigma factor (sigma 54) that recruits the core RNA polymerase to promoters of genes. In bacteria, RpoN has diverse physiological functions. In rhizobia, RpoN plays a key role in the transcription of nitrogen fixation (nif) genes. The Bradyrhizobium sp. DOA9 strain contains a chromosomal (c) and plasmid (p) encoded RpoN protein. We used single and double rpoN mutants and reporter strains to investigate the role of the two RpoN proteins under free-living and symbiotic conditions. We observed that the inactivation of rpoNc or rpoNp severely impacts the physiology of the bacteria under free-living conditions, such as the bacterial motility, carbon and nitrogen utilization profiles, exopolysaccharide (EPS) production, and biofilm formation. However, free-living nitrogen fixation appears to be under the primary control of RpoNc. Interestingly, drastic effects of rpoNc and rpoNp mutations were also observed during symbiosis with Aeschynomene americana. Indeed, inoculation with rpoNp, rpoNc, and double rpoN mutant strains resulted in decreases of 39, 64, and 82% in the number of nodules, respectively, as well as a reduction in nitrogen fixation efficiency and a loss of the bacterium's ability to survive intracellularly. Taken together, the results show that the chromosomal and plasmid encoded RpoN proteins in the DOA9 strain both play a pleiotropic role during free-living and symbiotic states.